Selective logging simulations and male fecundity variation support customisation of management regimes for specific groups of dipterocarp species in Peninsular Malaysia - N. Tani (2018)
© Forest Research Institute Malaysia. Modelling based on paternity analysis of one hill and three lowland dipterocarp timber species in Malaysia indicated that more pollen donors sired progeny in Shorea leprosula and S. parvifolia than in S. curtisii and S. maxwelliana populations, because they start reproducing earlier. The relatively greater male fecundity of small S. leprosula and S. parvifolia trees also contributed to more rapid recoveries of outcrossing pollination following reductions in selective logging simulations. Furthermore, pollination by these trees significantly increases numbers of adult trees that contribute to mating as males, and hence maintenance of higher genetic diversity in S. leprosula and S. parvifolia populations. The variation in male fecundity of the dipterocarp species might be linked to variations in their turnover rates, wood density and (hence) optimal logging regimes. More specifically, species with low wood density (S. leprosula and S. parvifolia) grow faster, start reproducing at smaller sizes and can be harvested with the current selective logging protocol with minimal loss of diversity. In contrast, species with high wood density (S. curtisii and S. maxwelliana) grow more slowly, start reproducing at larger sizes and should be harvested with a less intensive protocol to maintain outcrossing pollination rates and genetic diversity in subsequent generations. The results showed that selective logging guidelines should be customised for specific groups of dipterocarp timber species according to their reproductive parameters and wood density.